The Slapstick Routine of Parisian Monumentalism: Robert Desnos and Jacques-André Boiffard’s “Pygmalion and the Sphinx” (1930) - Ursula Cornelia de Leeuw (Index Journal)
This essay considers the 1930 essay “Pygmalion and the Sphinx” by Robert Desnos, originally published alongside Jacques André-Boiffard’s photographs of Parisian monuments in the journal Documents. I focus on Desnos and Boiffard’s tragicomic depiction of the municipal council of Paris’ failure to reconcile a fragmented sense of national identity through the erection of public monuments. As implicated by its title, “Pygmalion and the Sphinx” compares the “statuemania” of the Third Republic to the Greek myth. As Desnos and Boiffard reveal, within the monumental form is an antagonism between the civic ideal of ‘Pygmalion’ and the brute substance of the statue’s material, or the Sphinx. This tension inevitably collapses the idealist endeavour of monumentalism; a moment of folly opened by the laughter it evokes. Boiffard focuses the pedestal of the monument, and the rigidity of its material when exposed against the urban landscape. These photographs launch a base materialist perspective repeated by Desnos in his comic imagination. This term is further contextualised by the writings of Georges Bataille in Documents, whereby laughter is integral to the critique of idealism. In this essay, I read Desnos and Boiffard alongside Bataille to illuminate how monumentalism prepares its toppling in the ‘fall’ of the slapstick’s laugh.